Dialectical Hermeneutics of Poetry and Narratives of Hatred and Intolerance Ahead of the Democratic Party - Mulyono, Mulyono; Prabaningrum, Dyah; Zustiyantoro, Dhoni (Journal of Language Development and Linguistics, 2025)
The political, social and cultural phenomena leading up to the general elections, both presidential and legislative elections are interesting to observe. The battle that endangers the existence of the Republic of Indonesia is precisely at the supporting or lower layers. The elites can easily say to maintain a peaceful atmosphere, but at the lower layers, narratives of mutual downfall are scattered in the social media universe. In discrediting opponents, it is not uncommon to upload intolerant expressions. The expression of intolerance is sometimes blatant, some are packaged with symbolic language, which only certain people can interpret depending on their intellectual, emotional and spiritual levels. Expressions that are presumed to have intolerant nuances can be in the form of short narratives, rather long, or relatively long, and also in the form of poetry. With a dialectical hermeneutic approach, the expressions in social media can be understood and interpreted.